Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18393/ejss.2016.2.121-131
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of rill erosion processes in lateritic upland region: A pilot study

Abstract: The present paper is based on field investigation and measurement of rill erosion processes at Rangamati Experimental Station (Medinipur, West Bengal in India). In rill experiments, three different natural rills were studies in field for understanding of the dynamics of soil erosion processes of a rill catchment area. Geometric and morphological characteristics of each rill catchment area were analyzed. Results showed the widening, deepening and extended of rills because of sidewall sloughing, knick-points and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Natural factors like the slope of the terrain (25.7%) and rainfall coupled with runoff (28.5%) emerge as predominant natural influential factors of soil erosion. Several studies have identified these factors as the primary causes of soil erosion (Belay and Mengistu, 2019); Leta and Megersa, 2021), while (Shit et al, 2015) confirmed that heavy rainfall and steep slopes were the primary and secondary causes of soil erosion, respectively. Additionally, the scarcity of land for farming and settlements is a significant factor contributing to the deforestation in the Nyabugogo drainage area (IWRM, 2017).…”
Section: What Are the Primary Causes Of Soil Erosion In The Nyabugogo...mentioning
confidence: 96%
“…Natural factors like the slope of the terrain (25.7%) and rainfall coupled with runoff (28.5%) emerge as predominant natural influential factors of soil erosion. Several studies have identified these factors as the primary causes of soil erosion (Belay and Mengistu, 2019); Leta and Megersa, 2021), while (Shit et al, 2015) confirmed that heavy rainfall and steep slopes were the primary and secondary causes of soil erosion, respectively. Additionally, the scarcity of land for farming and settlements is a significant factor contributing to the deforestation in the Nyabugogo drainage area (IWRM, 2017).…”
Section: What Are the Primary Causes Of Soil Erosion In The Nyabugogo...mentioning
confidence: 96%